2012
DOI: 10.1088/1751-8113/45/10/105306
|View full text |Cite
|
Sign up to set email alerts
|

On quantum advantage in dense coding

Abstract: Abstract-The quantum advantage of dense coding is studied, considering general encoding quantum operations. Particular attention is devoted to the case of many senders, and it is shown that restrictions on the possible operations on the senders' side may make some quantum state useless for dense-coding. It is shown, e.g., that some states are useful for dense coding if the senders can communicate classically (but not quantumly), yet they cannot be used for dense coding, if classical communication is not allowe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
48
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 33 publications
0
48
0
Order By: Relevance
“…Dense coding is a procedure where A sends her subsystem to B, and by doing so she is able to transmit more classical information than she could if the system is classical. In the most general dense-coding scenario (Horodecki et al, 2001;Horodecki and Piani, 2012;Winter, 2002), A encodes her message by means of general quantum operations (Λ A ⊗ I B )[ρ AB ] = ρ A B , and the quantum operation changes the dimension of…”
Section: Dense-coding Capacitymentioning
confidence: 99%
“…Dense coding is a procedure where A sends her subsystem to B, and by doing so she is able to transmit more classical information than she could if the system is classical. In the most general dense-coding scenario (Horodecki et al, 2001;Horodecki and Piani, 2012;Winter, 2002), A encodes her message by means of general quantum operations (Λ A ⊗ I B )[ρ AB ] = ρ A B , and the quantum operation changes the dimension of…”
Section: Dense-coding Capacitymentioning
confidence: 99%
“…Again, a quantum state is said to be dense codeable if the above quantity (A B) is strictly positive. It was shown in the paper by Horodecki [31] that it suffices to consider only the extremal TPCP maps in evaluating the infimum or supremum for the above quantity, owing to the concavity of the von Neumann entropy. It was also shown that the quantum advantage of dense coding may be nonadditive, although not proved definitely.…”
Section: Implications On the Quantum Advantage Of Dense Codingmentioning
confidence: 99%
“…It was shown to be satisfying the properties of a genuine measure of total correlation. Also, a monogamy relation involving the entanglement of purification and the quantum advantage of dense coding was given by Horodecki et al [31]. However, the conditions for the monogamy or polygamy nature of entanglement of purification have not been found yet.…”
Section: Introductionmentioning
confidence: 99%
“…Achieving this in a cheap and reliable way is essential to the development of future quantum technologies. They also reinforces the role of quantum discord as a beneficial and practically relevant quantity [29][30][31][32][33][34][35][36][37][38][39][40][41][42][43]: as discord appears to bound the entanglement gain and to allow for excessive entanglement distribution, it emerges as a key player of fundamental relevance in the context of quantum communication and networking.…”
Section: Discussionmentioning
confidence: 52%